Derivation of Fourier Coefficients
Derivation of Fourier Coefficients Swapnil Sunil Jain December 28, 2006
Derivation of Fourier Coefficients
As you know, any periodic function f(t) can be written as a Fourier series like the following
f(t) | = | c0+∞∑n=1ancos(ωnt)+bnsin(ωnt) | (1) |
where ωn=nω0 and ω0=2πT
In the process to find an explicit expression for the coefficients c0,an,bn in terms of f(t), we write (1) in a slightly different way as the following
f(t)= | c0+a1cos(ω1t)+a2cos(ω2t)+…+akcos(ωkt)+… | |||
+b1sin(ω1t)+b2sin(ω2t)+…+bksin(ωkt)+… | (2) |
where k is a positive integer.
In order to derive the coefficient c0, we take the integral of both sides of (2) over one period.
∫τf(t)𝑑t= | ∫τc0𝑑t+∫τa1cos(ω1t)𝑑t+∫τa2cos(ω2t)𝑑t+…+∫τakcos(ωkt)𝑑t+… | ||
+∫τb1sin(ω1t)𝑑t+∫τb2sin(ω2t)𝑑t+…+∫τbksin(ωkt)𝑑t+… |
where τ=[t0,t0+T]. After evaluating the above equation, all the integrals on the right side with a sine or a cosine term drop out (since the integral of a sine or cosine over one period is zero) and we get
∫τf(t)𝑑t= | c0∫τ𝑑t | ||
⇒∫τf(t)𝑑t= | c0(T) | ||
⇒c0= | 1T∫τf(t)𝑑t=1T∫t0+Tt0f(t)𝑑t |
Now, in order to find ak, we multiply both sides of (2) by cos(ωkt) and we arrive at
f(t)cos(ωkt)= | c0cos(ωkt)+a1cos(ω1t)cos(ωkt)+a2cos(ω2t)cos(ωkt)+…+akcos2(ωkt)+… | ||
+b1sin(ω1t)cos(ωkt)+b2sin(ω2t)cos(ωkt)+…+bksin(ωkt)cos(ωkt)+… |
Then we take the integral of both sides of the above equation over one period and we get
∫τf(t)cos(ωkt)𝑑t= | ∫τc0cos(ωkt)𝑑t+∫τa1cos(ω1t)cos(ωkt)𝑑t+∫τa2cos(ω2t)cos(ωkt)𝑑t+… | ||
+∫τakcos2(ωkt)𝑑t+…+∫τb1sin(ω1t)cos(ωkt)𝑑t+∫τb2sin(ω2t)cos(ωkt)𝑑t+… | |||
+∫τbksin(ωkt)cos(ωkt)𝑑t+… |
By using orthogonality relationships or by literally evaluating the above integrals, we get the following
∫τf(t)cos(ωkt)𝑑t= | ∫τakcos2(ωkt)𝑑t | ||
⇒∫τf(t)cos(ωkt)𝑑t= | ak(T2) | ||
⇒ak= | 2T∫τf(t)cos(ωkt)𝑑t=2T∫t0+Tt0f(t)cos(ωkt)𝑑t |
Now, the process of finding bk is similar. We multiply both sides of (2) by sin(ωkt) and we get
f(t)sin(ωkt)= | c0cos(ωkt)+a1cos(ω1t)sin(ωkt)+a2cos(ω2t)sin(ωkt)+…+akcos(ωkt)sin(ωkt)+… | ||
+b1sin(ω1t)sin(ωkt)+b2sin(ω2t)sin(ωkt)+…+bksin2(ωkt)+… |
Then we take the integral of both sides of the above equation over one period and we arrive at
∫τf(t)sin(ωkt)𝑑t= | ∫τc0cos(ωkt)𝑑t+∫τa1cos(ω1t)cos(ωkt)𝑑t+∫τa2cos(ω2t)cos(ωkt)𝑑t+… | ||
+∫τakcos(ωkt)sin(ωkt)𝑑t+…+∫τb1sin(ω1t)cos(ωkt)𝑑t+∫τb2sin(ω2t)cos(ωkt)𝑑t+… | |||
+∫τbksin2(ωkt)𝑑t+… |
By using orthogonality relationships or by literally evaluating the above integrals, we get the following
∫τf(t)sin(ωkt)𝑑t= | ∫τbksin2(ωkt)𝑑t | ||
⇒∫τf(t)sin(ωkt)𝑑t= | bk(T2) | ||
⇒bk= | 2T∫τf(t)sin(ωkt)𝑑t=2T∫t0+Tt0f(t)sin(ωkt)𝑑t |
Title | Derivation of Fourier Coefficients |
---|---|
Canonical name | DerivationOfFourierCoefficients1 |
Date of creation | 2013-03-11 19:30:41 |
Last modified on | 2013-03-11 19:30:41 |
Owner | swapnizzle (13346) |
Last modified by | (0) |
Numerical id | 1 |
Author | swapnizzle (0) |
Entry type | Definition |